Deep sequencing of small non-coding RNA highlights brain-specific expression patterns and RNA cleavage. Issue 12 (2nd December 2019) - Haack, Fiete; Trakooljul, Nares; Gley, Kevin; Murani, Eduard; Hadlich, Frieder; Wimmers, Klaus; Ponsuksili, Siriluck
ABSTRACT: With the advance of high-throughput sequencing technology numerous new regulatory small RNAs have been identified, that broaden the variety of processing mechanisms and functions of non-coding RNA. Here we explore small non-coding RNA (sncRNA) expression in central parts of the physiological stress and anxiety response system. Therefore, we characterize the sncRNA profile of tissue samples from Amygdala, Hippocampus, Hypothalamus and Adrenal Gland, obtained from 20 pigs. Our analysis reveals that all tissues but Amygdala and Hippocampus possess distinct, tissue-specific expression pattern of miRNA that are associated with Hypoxia, stress responses as well as memory and fear conditioning. In particular, we observe marked differences in the expression profile of limbic tissues compared to those associated to the HPA/stress axis, with a surprisingly high aggregation of 3´-tRNA halves in Amygdala and Hippocampus. Since regulation of sncRNA and RNA cleavage plays a pivotal role in the central nervous system, our work provides seminal insights in the role/involvement of sncRNA in the transcriptional and post-transcriptional regulation of negative emotion, stress and coping behaviour in pigs, and mammals in general.